Improved detection of sulphur dioxide in volcanic plumes using satellite-based hyperspectral infrared measurements: Application to the Eyjafjallajkull 2010 eruption - Walker, J; Carboni, E; Dudhia, A; Grainger, R (2012)
The explosive phase of the eruption of the Eyjafjallajkull volcano in Iceland beginning on 14 April 2010 caused extensive disruption to aviation in Europe with serious social and economic consequences. Despite its impact, the explosive phase was modest in size and the amount of sulphur dioxide (SO ) released was low. The potential of hyperspectral thermal infrared measurements to discriminate emissions from similar events by measuring SO is examined using the Infrared Atmospheric Sounding Interferometer (IASI) on board MetOp-A. The transported plume in the initial stages of the explosive phase contained low amounts of SO at low altitude which placed it at the detection limit of space-based sensors used to monitor the volcanic threat to aviation using current methods. A recently developed technique for the fast retrieval of SO from IASI is applied in the context of the Eyjafjallajkull eruption to show that IASI is easily capable of sensing the SO in the plume at this stage where existing methods fail. The fast SO retrieval is calibrated against a fully quantitative optimal estimation retrieval of SO total column amount and plume altitude to derive the detection limit for the plume on 15 April 2010. An estimate of the general detection limit for the instrument is placed conservatively at 0.3 Dobson Units (DU) which is an order of magnitude lower than previously thought. Copyright 2012 by the American Geophysical Union.